2019
DOI: 10.3390/publications7020037
|View full text |Cite
|
Sign up to set email alerts
|

What Is an Institutional Repository to Do? Implementing Open Access Harvesting Workflows

Abstract: In 2016, Florida State University adopted an institutional Open Access policy, and the library staff were tasked with implementing an outreach plan to contact authors and collect publication post-prints. In 2018, I presented at Open Repositories in Bozeman to share our workflow, methods, and results with the repository community. This workflow utilizes both restricted and open source methods of obtaining and creating research metadata and reaching out to authors to make their work more easily accessible and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, the workflow helped to maintain an increase in the number of records of faculty-related scholarship, and Bull and Schultz (2018) emphasized its use in student worker support and future student staffing for sustainability, as well as to save time spent on organizing student training. Smart (2019) reported that a plan was devised by, the Office of Digital Research and Scholarship's librarian team to increase the low faculty self-submission rates to the repository, using a combination of metadata harvesting workflow, semi-automated metadata record creation, and outreach emails to inform researchers about the open access policy and encourage them to upload their manuscripts to the institutional repository. Lappalainen and Narayanan ( 2023) recently described a semi-automated workflow that used a custom R script to harvest and convert content from Scopus, Web of Science, Dimension, and Unpaywall into the repository.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the workflow helped to maintain an increase in the number of records of faculty-related scholarship, and Bull and Schultz (2018) emphasized its use in student worker support and future student staffing for sustainability, as well as to save time spent on organizing student training. Smart (2019) reported that a plan was devised by, the Office of Digital Research and Scholarship's librarian team to increase the low faculty self-submission rates to the repository, using a combination of metadata harvesting workflow, semi-automated metadata record creation, and outreach emails to inform researchers about the open access policy and encourage them to upload their manuscripts to the institutional repository. Lappalainen and Narayanan ( 2023) recently described a semi-automated workflow that used a custom R script to harvest and convert content from Scopus, Web of Science, Dimension, and Unpaywall into the repository.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the constant labor of working with researchers to identify opportunities for open interventions in their work and interpreting and translating cryptic publisher self-archiving policies, libraries invested deeply in the human (bio/organic + plus a soul!) infrastructure of repository managers/coordinators, scholarly communication librarians, and developers focused on customizing repository platforms to accomodate 6-36 month embargos, automagical workflows, and faceted search (Smart, 2019). Then, Clifford Lynch, the oracle of open, goes and flips the script by updating the agenda, such that "the linkage between journal article open access and institutional repository agendas has been a mistake, and one that has resounded to the detriment of both agendas" (Lynch, 2017).…”
Section: Continued On Page 18mentioning
confidence: 99%
“…There have been past efforts at developing a linked data native OAI-PMH successor that could be more effectively queried on the fly [4,5], but to date, these have not materialized on a sufficient scale. Most recent efforts have focused on building sufficiently large local databases of harvested OAI-PMH endpoints that can then be indexed with ElasticSearch through a unified discovery portal [6]. These portals are usually supported at the national level, with Australia's National Data Service [7,8] as a prominent example.…”
Section: Literature Reviewmentioning
confidence: 99%